The Effects of Internet on Rural-to-Urban Migrating Intentions of Young Villagers: Evidence from Rural Indonesia - Iwana, Meriko Dian Candra; Hidayat, AR. Rohman Taufiq; Dinanti, Dian; Onitsuka, Kenichiro (AGRARIS: Journal of Agribusiness and Rural Development Research, 2022)
Indonesian’s government attempts to build internet infrastructure covering all rural areas of which most internet users are young. Youths refer to a generation who intuitively able to operate internet device and are supposed to take an important decision about their future careers, occupations, and living places. This study aimed to identify effects of internet on rural-to-urban migrating intentions of rural youths. The Structural Equation Model-Partial Lease Square (SEM-PLS) approach was applied. This study involved 866 of 15 to 24 years villagers of Tumpukrenteng Village, Malang Regency. This village reflects an ordinary village which is characterized high rural-to-urban migration. A randomized of 213 respondents were taken but 193 respondents were analyzed due to internet users. The independent variables covered internet infrastructure, internet usage, collecting information on prospective destination activity, and the dependent variable covered migrating intention. The results demonstrated that internet accelerated young villagers’ rural migrating intention. Internet allowed their users to access information of prospective destination. This research suggested young villagers to apply internet into economic benefits activity, such as e-commerce and to reduce adverse impacts of internet usage and rural youth’s emigration.